Filogeografia de Aegla longirostri (crustacea, decapoda, anomura) - Crivellaro, Marcelo Schüler (2017)
Aegla is the most diverse genus of freshwater crabs in southern South America. The Aeglidae family, which belongs to this genus, has a marine origin, with two fossil genera, found in marine sediments in New Zealand and Mexico. Currently, 83 species of Aegla are known to occur in the watersheds of Brazil, Argentina, Bolivia, Chile, Paraguay and Uruguay, being found from 320 meters of depth to 3.500 meters of altitude. Approximately 70% of Aegla species are as endangered, mainly due to the rapid degradation of the aquatic environment combined with the restricted distribution of most species. Despite the high number of species described, their diagnostic morphological characters exhibit little variation resulting in difficulties in correctly identifying the species. In addition, the occurrence of cryptic species in eglids has already been suggested. Identifying cryptic species is essential for more accurate estimates of biodiversity, to understand the processes that lead to life diversification, and also for the correct direction of conservation efforts, if any are threatened. Molecular and geometric morphometric evidence suggest that the nominal species Aegla longirostri is formed by a complex of species, deserving attention in relation to its real distribution, endemicity and conservation status. One tool that has proven to be successful in revealing cryptic biodiversity is phylogeography. Using various molecular techniques and analytical methods, phylogeography tests hypotheses about the causal relationship between geographic phenomena, species distributions, and the mechanisms that lead to speciation. The present dissertation aims to estimate phylogenetic relationships and phylogeographic patterns of Aegla longirostri populations, and thus test a hypothesis that they form a complex of cryptic species. If it is a species complex, identify how many and which populations make up the potential cryptic species. In addition, we aimed to analyze the genetic structure of the populations using two mitochondrial molecular markers (COI and 16S) and a nuclear molecular marker (intron of the ANT gene), in order to understand which historical processes may have influenced the distribution of the genetic lineages. 17 populations of A. longirostri were analyzed and the results confirmed the hypothesis proposed, wherein, species delimitation methods indicated that the complex is formed by at least 14 possible species. In addition, the observed results suggest a possible contribution of the landscape topography in the diversification of this complex. Future studies that seek to find new diagnostic characters or new techniques for the delimitation of Aegla species are necessary. The real diversity of the genus is still underestimated and it is essential to accurately quantify its hidden diversity and, therefore, to apply more effective measures for the management and conservation of biodiversity.